2005
DOI: 10.1002/marc.200500649
|View full text |Cite
|
Sign up to set email alerts
|

A General Strategy for Nano‐Encapsulation via Interfacially Confined Living/Controlled Radical Miniemulsion Polymerization

Abstract: Summary: We propose and demonstrate the utility of an interfacial living/controlled (reversible addition fragmentation chain transfer, RAFT) radical miniemulsion polymerization in nano‐encapsulation. The principles and methodology behind this technique are readily scalable and highly efficient. The living/controlled nature of the system offers great opportunities to tune the properties of the polymer shell‐like thickness, surface functionality, molecular weight, and inner‐wall functionality by simply using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 21 publications
0
76
0
3
Order By: Relevance
“…[35] Furthermore, amphiphilic macro-RAFT agents based on poly(acrylic acid) and polystyrene or poly(butyl acrylate) ( Table 1, entry 2) were used as the sole stabilizer of monomer droplets in miniemulsion polymerization. [37] Y-shaped macromonomers based on poly[(dimethylamino)ethyl methacrylate] (PDMAEMA) ( Table 1, entry 4), synthesized by oxyanion-initiated polymerization using a difunctional potassium alcoholate initiator trimethylol propane allyl ether, were used as pH-responsive surfmers in the miniemulsion polymerization of styrene. [36] In another example a cooligomer RAFT agent was used based on styrene and amminolyzed maleic anhydride (SMA-RAFT agents, Table 1, entry 3) for a controlled radical miniemulsion polymerization at the droplets interface for the preparation of PS colloids.…”
Section: Surfmers/inisurfs/transsurfsmentioning
confidence: 99%
“…[35] Furthermore, amphiphilic macro-RAFT agents based on poly(acrylic acid) and polystyrene or poly(butyl acrylate) ( Table 1, entry 2) were used as the sole stabilizer of monomer droplets in miniemulsion polymerization. [37] Y-shaped macromonomers based on poly[(dimethylamino)ethyl methacrylate] (PDMAEMA) ( Table 1, entry 4), synthesized by oxyanion-initiated polymerization using a difunctional potassium alcoholate initiator trimethylol propane allyl ether, were used as pH-responsive surfmers in the miniemulsion polymerization of styrene. [36] In another example a cooligomer RAFT agent was used based on styrene and amminolyzed maleic anhydride (SMA-RAFT agents, Table 1, entry 3) for a controlled radical miniemulsion polymerization at the droplets interface for the preparation of PS colloids.…”
Section: Surfmers/inisurfs/transsurfsmentioning
confidence: 99%
“…According to the targeted applications and experimental conditions, several particles morphologies can be designed such as core-shell and hollow particles. RAFT miniemulsion polymerization has recently proven to be an efficient technique to synthesize nanocapsules, as reported by Luo and co-workers [180][181][182] who developed amphiphilic macroRAFT agents to both control and stabilize interfacially confined miniemulsion polymerization. They first used styrene and maleic anhydride oligomers (SMA-RAFT) synthesized by PEPDTA-mediated RAFT copolymerization [180,182].…”
Section: Nanocapsules Synthesized By Raft Miniemulsion Polymerizationmentioning
confidence: 99%
“…Recently, to directly encapsulate V. Mittal (ed.) Miniemulsion Polymerization Technology, (97-138) © Scrivener Publishing LLC liquid substances via a synthetic method in the emulsion, microemulsion, or miniemulsion has showed to be promising to synthesize nanocapsules [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], The formation of nanocapsules with an oily core in most literatures followed the mechanism of polymer phase separation in the oil droplets during polymerization. This process is controlled by the thermodynamic and kinetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Scott et al reported an analogical method to the interfacial polycondensation for synthesizing nanocapsules but via alternating free radical copolymerization of hydrophobic maléate and hydrophilic vinyl ether monomers on the interfaces of the oil droplets in miniemulsion [22][23]. In addition, Luo et al reported that the targeted nanocapsules could be synthesized via the interfacially confined controlled/living radical miniemulsion polymerization by using an amphiphilic RAFT agent [24][25][26]. Thermo-sensitive polymers such as poly(N-isopropylacrylamide) (PNIPAM) can undergo volume phase transition to separate out of the aqueous phase above their low critical solution temperature (LCST).…”
Section: Introductionmentioning
confidence: 99%